The Principle of Freedom of Contract, Pre-Contractual Obligations Legal Review English, EU and US Law - Tedoradze Irakli (European Scientific Journal, ESJ, 2017)
The impregnable foreign policy of Georgia is to become a full and equal member of the world. Over the past decade the country has been actively trying to integrate into the European economy, to regulate and harmonize the legal space, which will help the state to become attractive both for the world community, as well as potential investors and significantly strengthen its position in the domestic economy. A step forward in this direction may be considered signing the EU association agreement. This event clears the way to Europe for the business of Georgia. Therefore, it is extremely important to establish the proven regulations of Europe and to develop the legal space in compliance with international standards. All of this, of course, require legislative changes within the country in terms of its development, improving and adaptation, especially civil, antitrust, antidumping and competition regulatory legislation.